You Scratch my Back, and I'll Scratch Yours: Feedback and Recommendation on Freelance Translators Recruitment - Hemn Mohammed Ali Mahmood (Zanco Journal of Humanity Sciences)
Professional translation is now mostly conducted in virtual teams, or production networks, where freelance translators and language service providers (LSPs) communicate via increasingly computerized means. This study examined how feedback are left on profiles and specifically to find extent to which these feedbacks have been manipulated by having a prior agreement with each other (the translation agency and freelancer translator). This study was a multiple-case study since it covered Upwork and Proz.com, and an ethnographic was employed since a cultural context was used for the identification of the websites. Proz.com and Upwork were chosen to investigate and collect the data as both are the most effective websites for freelancers among all other workplace websites. Unstructured observation and semi-structured interviews were carried out for the data collection. The results showed that the vast majority of the feedback on profiles have been biased. In most cases, a settlement between the translation agency and freelancers was made before leaving the feedback. In other words, the feedback should not be depended on when a freelance translator needs to work for a company and vice versa.